2011
DOI: 10.1007/s11010-011-0961-8
|View full text |Cite
|
Sign up to set email alerts
|

CK2α is essential for embryonic morphogenesis

Abstract: CK2 is a highly conserved serine-threonine kinase involved in biological processes such as embryonic development, circadian rhythms, inflammation and cancer. Biochemical experiments have implicated CK2 in the control of several cellular processes and in the regulation of signal transduction pathways. Our laboratory is interested in characterizing the cellular, signaling and molecular mechanisms regulated by CK2 during early embryonic development. For this purpose, animal models, including mice deficient in CK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 52 publications
0
38
1
1
Order By: Relevance
“…The forelimb and hindlimb buds are hypoplastic in CK2α knockouts [ 18 ]; however, we did not observe an apparent difference in the epithelium or mesenchyme of the limb buds compared to wild type.…”
Section: Histological Analysis Of Ck2α Knockoutscontrasting
confidence: 80%
See 2 more Smart Citations
“…The forelimb and hindlimb buds are hypoplastic in CK2α knockouts [ 18 ]; however, we did not observe an apparent difference in the epithelium or mesenchyme of the limb buds compared to wild type.…”
Section: Histological Analysis Of Ck2α Knockoutscontrasting
confidence: 80%
“…In addition, the division between the heart chambers in the CK2α knockout is not as apparent as in the wild type. The somites (precursors of body muscles and vertebra) in CK2α knockout mice at E9.5 are hypoplastic, particularly the posterior somites [ 18 ]. In addition, our histological analysis showed that the cellular organization of the somites is abnormal.…”
Section: Histological Analysis Of Ck2α Knockoutsmentioning
confidence: 78%
See 1 more Smart Citation
“…There is some indication that CK2 plays a role in spermatogenesis [8,7,23] as well as during certain stages of embryogenesis [24,25]. Furthermore, it was shown by several groups that CK2 seems to be an important protein kinase for a variety of different cellular processes in developing organs and organogenesis [5,6,26,27]. In the differentiation of pre-adipocytes into adipocytes, CK2 was found to be accompanied by a decrease in the protein level and in the kinase activity [28,29].…”
mentioning
confidence: 99%
“…17) It was reported to be implicated in a series of physiological and pathological processes, including various cancers, 18) bone formation, 19) mouse globozoospermia, 15) embryonic morphogenesis, 20) and chronic intestinal inammation. 21) We have previously identified CK2 as a GN-related gene and indicated that CK2 could be a therapeutic target for treating GN.…”
Section: Discussionmentioning
confidence: 99%